Evaluation of Acetylfentanyl Following Suspected Heroin Overdose When Complicated by the Presence of Toxic Fentanyl and Alprazolam Concentrations. Issue 3 (September 2019) - Fagiola, Michael; Hahn, Timothy; Avella, Joseph
A 34-year-old male was reported to be snorting a white powder that was believed to contain heroin. Toxicological analysis revealed free morphine (356 μg/L), fentanyl (34.7 μg/L), alprazolam (64.9 μg/L), and acetylfentanyl (32.9 μg/L) in femoral blood and 6-monoacetylmorphine (6-MAM, <10.0 μg/L) in vitreous fluid. Norfentanyl was only detected in stomach contents (<1.00 μg/total). Heroin, fentanyl, and acetylfentanyl were also detected in solid dose evidence submitted by law enforcement. The fentanyl and alprazolam concentrations might normally be associated with a fatal outcome and are supported with the distribution of fentanyl and alprazolam being consistent with an acute intoxication. In addition, the presence of 6-MAM and a free versus total morphine ratio of 67.9% provide supporting evidence of a rapid death following intranasal (IN) administration. However, the presence of illicit acetylfentanyl complicates toxicologic interpretation due to overlapping recreational and fatal concentrations of this compound reported in the literature as well as a potential for postmortem redistribution (PMR). Reported acetylfentanyl concentrations have also varied when presented with significant fentanyl concentrations and underscore the need to consider a wide range of illicit opioid compounds when investigating drug-related deaths. Based on our comprehensive toxicologic analysis, the results suggest an acute intoxication primarily by IN administration of acetylfentanyl and fentanyl. In addition, we suggest the presence of alprazolam, 6-MAM, and a percentage free morphine is also consistent with rapid death. The cause of death was officially attributed to an acute combined intoxication of acetylfentanyl, fentanyl, alprazolam, and heroin, with the manner of death as accidental.